Effectiveness of peer support programmes for improving well‐being and quality of life in parents/carers of children with disability or chronic illness: A systematic review - Lancaster, Katharine; Bhopti, Anoo; Kern, Margaret L.; Taylor, Rachel; Janson, Annick; Harding, Katherine (Child : care, health & development, 2023)
Aim This systematic review synthesized quantitative evidence from the past decade of the effectiveness of peer support programmes in improving the well‐being and/or quality of life (QoL) for parents/carers of children with disability/chronic illnesses. Background For children with disability or chronic illness, parents/carers are critical in enabling or limiting their child's development. The parent's/carer's ability to provide the necessary responsive and structured care is impacted by several factors, including their own personality, skills, resources and well‐being. Peer support programmes often aim to build parent/carer and/or family capabilities. Although studies and reviews have found positive benefits arising from such programmes, the impact of such programmes, specifically on well‐being and QoL, is unknown Results Quantitative studies published between 2011 and 2020 that examined the impact of programmes with a significant peer support component on parental/carer well‐being, QoL and/or distress were identified from four databases and were searched and yielded 3605 articles, with 13 articles meeting the inclusion criteria. The results suggested that peer support is effective for reducing distress and improving the well‐being and QoL among parents of children with disabilities; however, the evidence is limited by a high risk of bias in the included studies. Conclusions Although existing evidence suggests that programmes for parents/carers with a significant peer support component are beneficial for well‐being and QoL, rigorous methodologies are needed in the future to gain a better understanding of the benefits of such programmes.